محددات دالتي الطلب و العرض السياحي - أحسن, صليحة (My University, 2014)
الملخص: *على اعتبار أن السياحة أحد القطاعات الهامة التي تقوم عليها اقتصاديات كثير من الدول وتمت قطا السياحة في الجزائر بمؤهلات و طاقات هائلة و تحاول السياسية الاقتصادية الجزائرية استغلالها في الآونة الأخيرة من أجل الارتقاء و الدف بعجلة التنمية الاقتصادية من خلال الرف من جودة الخدمات السياحية المقدمة التركيز على إعداد مخططات استراتيجية تحدد مسار السياحة مستقبلا و تحسين وضعيتها التنافسية في السوق السياحي العالمي و بتسليط الضوء على تجارب بعض الدول في السياحة بذلك فالإشكالية حول أهم محددات دالتي العرض و الطلب السياحي بالجزائر و ببناء نموذج قياسي لأهم المتغيرات المؤثرة و معرفة آفاقها. الكلمات المفتاحية: : السوق السياحية ،الطلب و العرض السياحي ،التوازن السياحي، بناء نموذج قياسي. Abstract: *on tourism as one of the important sectors of the economies of many States and enjoy the tourism sector in Algeria qualifications and enormous energies and try to Algerian political and economic exploitation in recent times in order to upgrade the and push economic development through the lifting of the quality of tourism services provided by a focus on the preparation of the Strategy Outlines determine the course of future tourism and improve their competitiveness in world tourism market and by highlighting the experiences of some States in tourism so problematique was on the most important determinants functions supply and tourism demand in Algeria and built a model record of the most important variables affecting and expected future prospects. Keywords: tourist market, demand and supply tourism, balance tourism, construction of a model statistic. a consideration That tourism the most important in the bases of economic Enjoy the tourism sector in Algeria qualifications and great potential , especially ones with character Desert And trying to exploit the political economic Algerian recently in order to improve and push forward the economic development by focusing on the preparation of strategic plans determine the course of future tourism And improve the situation of competitiveness in the tourism market globally. concentration
دراسة حالة الجزائر في الفترة الممتدة -1990-2014
Keywords: السوق السياحية -الطلب - العرض السياحي -التوازن السياحي-بناء نموذج قياسي